Залізодобувне виробництво на території України та Угорщини на рубежі І—II тис. н. е. - Бідзіля, В.І.; Паньков, С.В. (Археологія, 2000)
Досліджується один із типів залізодобування, поширений на території України та Угорщини, і зазначений авторами як Григорівка-«Imola», існування якого свідчить про загальну традицію в розвитку технологічної культури обох народів в період раннього середньовіччя. На основании изучения остатков одного из типов железообрабатывающих горнов, зафиксированных на территории Украины (Григоровка, Кременище) и Венгрии (тип «Imola»), датированных последней четвертью I тыс.— первой четвертью II тыс, н. э., авторы рассматривают вопросы реконструкции и продуктивности горнов, организации производства железа, происхождения и значения в развитии черной металлургии раннефеодальных государств, существовавших в то время как на территории современной Украины, так и Венгрии. Based on the study the remnants of one type of iron making furnaces which were investigated at territories of Ukraine (Grigorovkh, Kremenysche) and Hungary (Imola type) and dated to the last quarter of the second century AD, the authors discern some issues concerning their modeling and productivity, arrangement of iron making, the origin and the importance of the early feudal states (existed at that time at the territories of Ukraine and Hungary) in the development of a ferrous metallurgy.